2016
DOI: 10.1155/2016/5654129
|View full text |Cite
|
Sign up to set email alerts
|

Benzene Removal by Iron Oxide Nanoparticles Decorated Carbon Nanotubes

Abstract: In this paper, carbon nanotubes (CNTs) impregnated with iron oxide nanoparticles were employed for the removal of benzene from water. The adsorbents were characterized using scanning electron microscope, X-ray diffraction, BET surface area, and thermogravimetric analysis. Batch adsorption experiments were carried out to study the adsorptive removal of benzene and the effect of parameters such as pH, contact time, and adsorbent dosage. The maximum removal of benzene was 61% with iron oxide impregnated CNTs at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…In recent years, multiwalled carbon nanotubes (CNTs) have been explored widely due to their unique properties [24–26] and have been extensively used in nanotechnology, optics, electronics, material science, and water treatment [27]. CNTs were also reported for the adsorption of heavy metal ions [2832] and organic compounds [3336]. Despite the most recent comprehensive review articles and to the best of our knowledge, no studies were reported on the use of multiwalled carbon nanotubes for Se removal.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, multiwalled carbon nanotubes (CNTs) have been explored widely due to their unique properties [24–26] and have been extensively used in nanotechnology, optics, electronics, material science, and water treatment [27]. CNTs were also reported for the adsorption of heavy metal ions [2832] and organic compounds [3336]. Despite the most recent comprehensive review articles and to the best of our knowledge, no studies were reported on the use of multiwalled carbon nanotubes for Se removal.…”
Section: Introductionmentioning
confidence: 99%
“…CrCl 3 , in the first step, then was continued by calcination of biochar-CrCl 3 composite to form biochar-Cr 2 O 3 composite. Some previous researchs have called this way of modification by term of impregnation [18,19,20].…”
Section: Characterization Of the Composites Using X-ray Diffractionmentioning
confidence: 99%
“…CNTs are an important carbon‐based adsorptive material with exceptional adsorption capabilities and high adsorption efficiency for various organic pollutants . CNTs are particularly promising as a benzene adsorbent for environmental protection/remediation . For example, in the study of Abbas et al CNTs impregnated with iron oxide nanoparticles were employed for the removal of benzene from water.…”
Section: Introductionmentioning
confidence: 99%
“…CNTs are particularly promising as a benzene adsorbent for environmental protection/remediation . For example, in the study of Abbas et al CNTs impregnated with iron oxide nanoparticles were employed for the removal of benzene from water. Elsehly et al investigated the performance of CNT‐based filter for benzene removal from aqueous solutions, and they indicated that the filters were efficient for benzene removal.…”
Section: Introductionmentioning
confidence: 99%